Koncepcja dobrowolnego ubóstwa w pismach monastycznych św. Augustyna - Kasprzak, Dariusz (Vox Patrum, 2013)
The first coherent doctrine of voluntary poverty appeared in Western Church theology in the writings of St. Augustine. This idea developed gradually under the influence of the coenobitic ideal and vision of a community Church. First having excluded the Manichean vision of community (AD 386-396) St. Augustine adopted the coenobitic conception of poverty (relinquishing individual possession in favour of communal ownership and working for the benefit of the community). In his mature period (AD 397-426) St. Augustine referred directly to the perfect vision of the Christian monastic community described in Acts 4:32-36 as the source of voluntary poverty. In this way the monks copied the perfection of the Early Church community. One might say his approach to ascetic poverty was according to the principle of qualitative parity i.e. every monk receives the minimum of material necessities. St. Augustine’s sermons 355 from December AD 425/January AD 426 and 356 from January AD 426 show clearly how he and his brothers practiced individual and community poverty.